Pharmacodynamic and pharmacokinetic effects and safety of verinurad in combination with febuxostat in adults with gout: a phase IIa, open-label study. Issue 1 (9th April 2018) - Fleischmann, Roy; Winkle, Peter; Hall, Jesse; Valdez, Shakti; Liu, Sha; Yan, Xiaohong; Hicks, Liz; Lee, Caroline; Miner, Jeffrey N; Gillen, Michael; Hernandez-Illas, Martha
Abstract : Objective: Verinurad (RDEA3170) is a high-affinity, selective URAT1 inhibitor in development for treating gout and asymptomatic hyperuricaemia. This study evaluated the pharmacodynamics, pharmacokinetics and safety of verinurad in combination with febuxostat in adults with gout. Methods: The phase IIa, open-label, multicentre study randomised 64 subjects into one of five cohorts to receive febuxostat (40 or 80 mg) alone or in combination with verinurad 2.5–20 mg. Serial plasma/serum and urine samples were assayed for verinurad and uric acid. Safety was assessed by adverse events, chemistry panels, ECGs and physical examinations. Results: Serum pharmacodynamic data demonstrated the maximum percent decrease in serum urate (sUA) from baseline (Emax ) at 8–12 hours after dosing. Verinurad with febuxostat decreased sUA in a dose-dependent manner. Emax for verinurad with febuxostat 40 mg ranged from 52% to 77% vs 42% for febuxostat 40 mg alone; Emax for verinurad with febuxostat 80 mg was 62%–82% vs 55% for febuxostat 80 mg alone. Urinary uric acid excretion rate was reduced below baseline by febuxostat alone and was comparable to baseline for verinurad with febuxostat. Verinurad plasma exposure increased with dose and was comparable when combined with febuxostat. No drug-drug interactions were observed. Verinurad was well tolerated with no clinically meaningful changes in laboratory values. Conclusion: Verinurad administered with febuxostat produced dose-dependent decreases in sUA while maintaining urinary uric acid levels comparable to baseline. These dose combinations of verinurad and febuxostat were generally well tolerated. These data support continued investigation of oral verinurad in patients with gout. Trial registration number: NCT02246673